Working From Home Under COVID-19: Who Is Affected? Evidence From Latin American and Caribbean Countries - Isaure Delaporte; Werner Pe\~na (Global Labor Organization (GLO), 2020)
Millions of individuals are required to work from home as part of national efforts to fight COVID-19. To evaluate the employment impact of the pandemic, an important point is whether individuals are able to work from home. This paper estimates the share of jobs that can be performed at home in 23 Latin American and Caribbean (LAC) countries as well as examines the workers' characteristics associated with such jobs. To carry out this analysis, this paper uses rich harmonised household surveys and presents two measures of teleworkability. The first measure of the feasibility of working from home is borrowed from Dingel and Neiman (2020), while the second closely follows the methodology of Saltiel (2020). We use the second measure as our benchmark, as it is based on a more representative task content of occupations for LAC countries. We find that the share of individuals who are able to work from home varies from 7% in Guatemala to 16% in the Bahamas. We document considerable variation in the potential to work from home across occupations, industries, regions and workers' socioeconomic characteristics. Our results show that some individuals are better positioned to cope with the current situation than others. This highlights the need to assist the most vulnerable workers in the context of the global pandemic.
Keywords: 330; COVID-19; Teleworking; Employment; Demographics